Stochastic Behaviour of Single Unit System with Preventive Maintenance subject to Random Appearance of Server - Gitanjali (International Journal of Computer Sciences and Engineering, 2025)
In this paper using Semi-Markovian approach a reliability model of single unit is develop. Unit works in operative mode initially and goes for preventive maintenance after a pre-specific time of operation. Single repairperson that may be appear and disappear randomly does every repair work including preventive maintenance. New one replaces the failed unit in case its repair is not possible by the server in a given fixed repair time. The repair activities and repairperson (server) are perfect. The random variables associated with failure time of the unit and different repair activities are independent to each other. The failure time and maximum operation time of the unit are exponentially distributed while the distributions of time of appearance and disappearance of server, repair and replacement of the unit are taken as arbitrary with different probability density functions. Applying regenerative point techniques, different reliability attributes are obtained to enhance the performance of system. Numerical results of Mean time to system failure (MTSF), Availability and profit function that are very much helpful to system engineer have also been analysed.